Terminal phase of bird schistosomiasis caused by Trichobilharzia regenti (Schistosomatidae) in ducks (Anas platyrhynchos f. domestica) - Chanová, Marta; Horák, Petr (Folia parasitologica, 2007)
The terminal phase of the migration of Trichobilharzia regenti Horák, Kolárová et Dvorák, 1998 in the definitive host (Anas platyrhynchos f. domestica) was studied 12-27 days post infection (p.i.). Brain meninges were the last part of the nervous system where the worms were detected before their occurrence in the nasal cavity. In meninges, the parasites started to feed on red blood cells. Then the worms occurred in the nasal mucosa 14-25 days p.i. and the first immature eggs appeared 15 days p.i. The fully developed miracidia were recorded in the eggs from 17 days p.i. and freely in the nasal mucosa 19 days p.i. Infiltrates of lymphocytes, later also eosinophils and heterophils around the eggs and free miracidia, were observed from 15 and 19 days p.i., respectively. The haemorrhages occurring from 17 days p.i., and the granulomas with lymphocytes, eosinophils and heterophils forming around the eggs from 22 days p.i. were the most apparent pathological changes of nasal tissue.
Keywords: kachny; Nasal Mucosa; Schistosomiasis; krvácení; zvířata; Meninges; nemoci drůbeže; Hemorrhage; Schistosomatidae; Animals; Eosinophils; schistosomóza; lymfocyty; Granuloma; Lymphocytes; eozinofily; meningy; Poultry Diseases; Ducks; nosní sliznice; granulom